PEOPLE WITH HIV WITH NORMAL VERSUS ABNORMAL CAROTID ARTERY ULTRASOUND AND IMPLEMENTATION OF MEDICAL THERAPY FOR CAROTID ARTERY STENOSIS - Karla L. Inestroza; Vanessa Hurtado; Michaela E. Larson; Bertrand F. Ebner; Jelani Kayode Grant; Louis Vincent; Maria Alcaide; Barry Hurwitz; Catherine Boulanger; Alexis Powell; Dushyantha Jayaweera; Claudia A. Martinez (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD in Special Populations Background: Atherosclerosis is a significant cause of cardiovascular disease (CVD). People with HIV (PWH) have a greater risk of CVD and vascular events, including myocardial infarction (MI) and ischemic stroke. A strong association has been described between CAS in PWH, but the mechanism is incompletely understood. Methods: We performed a retrospective chart review of patients who received care at University of Miami/Jackson Memorial Hospital HIV clinics between 2017-2019 (N=1,166) and stratified patients into PWH with Normal Carotid Artery Ultrasound (CAUS) and Abnormal CAUS. PWH with Abnormal CAUS (N=24) was defined as patients with any degree of CAS reported by CAUS. PWH with Normal CAUS (N=13) was defined as patients with no CAS reported by CAUS. Data regarding demographic, clinical, imaging, and laboratory results was obtained. Results: The prevalence of PWH with CAS was 2.1%. PWH with an Abnormal CAUS were significantly older (63.7years vs. 55.5 years, p=0.049) and had a lower absolute CD8 count (700.2 cells/mm3 vs. 955.1 cells/mm3, p=0.037) compared to PWH with a Normal CAUS. Baseline characteristics are described in Table 1.Regarding the medical management of PWH who had CAS, 4.2% of patients were on Aspirin, 58.3% were on a statin, and no patients were on anticoagulation. 70.8% of PWH with CAS were on hypertension treatment, and of those, 33.3% were on a beta-blocker medication, 20.8% were on an angiotensin-converting enzyme inhibitor, and 33.3% were on an angiotensin receptor blocker. Conclusion: We found a CAS prevalence of 2.1%, greater than reported for the general population (1.5% Lancet 2020). Traditional CVD risk factors and HIV-related factors alone do not explain this finding. 4.2% of PWH CAS were on Aspirin (Class I recommendation for all patients with CAS), and 58.3% were on a statin (Class IA recommendation). Appropriate medical therapy needs to be emphasized in those with CAS to reduce the risk of vascular complications. The small sample size limits the results of this study, and further studies are needed to understand the risk factors and mechanisms leading to increased risk of vascular events and CVD in this population.